Testing the validity of the Relative Strength Index to make a trade decision on the shares listed on the Damascus Securities Exchange - زهره شادي (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aims to test the validity of using the relative strength index for trading on the shares of companies listed on the Damascus Securities Exchange during the period between 2020 and 2022. The research was conducted on the most active companies based on what was mentioned in the two annual reports for the years 2020 - 2021 of the Damascus Stock Exchange, Backtesting methodology was used as a tool to test the validity of the RSI as a trading strategy by making a comparison between trading using the RSI and trading using the stock price, The comparison was made at two levels of the RSI boundary (30-70) (20-80)The research indicated that it is not possible to rely on the relative strength index in making a decision to trade on stocks in the Damascus Stock Exchange in general, with the possibility of relying on it when trading on some stocks.